An Approach to Identify Problematic Nodes Based on Threshold in Mobile Ad-Hoc Networks - Nitin Tyagi1, Manas Kumar Mishra (International Journal of Advanced Science and Technology, 2020)
Mobile ad hoc network is not needed any pre-existing infrastructure or central administration. The term "Ad-Hoc" means self-sorted out node that don’t have a focal substance to represent them. So, because of no boundaries it’s critical to secure network from attack. Security is serious issue for current research on MANET. In MANETs employ customary method for security to ensure the systems through firewalls and encryption programming, which is never again powerful and adequate. With a specific end goal to give extra security to the MANETs, intrusion detection mechanisms ought to be included. In this paper, a quantitative strategy for identifying problematic nodes in the MANETs is proposed. To pull around this abnormality, aim is to put forward a new detection technique. In proposed work introduced the concept of sequence number in presence of calculated threshold which identify multiple problematics node and send a warn message to source. Computer simulation presents the impact that proposed strategy is better for finding malicious node than the other existing methods. Keywords: MANET, Sequence number, Threshold.